Inter-protomer opening cooperativity of envelope trimers positively correlates with HIV-1 entry stoichiometry - Revansiddha H. Katte; Wang Xu; Yang Han; Xinyu Hong; Maolin Lu (mBio)
ABSTRACT HIV-1 entry to host cells is fulfilled by fusion, mediated by surface glycoprotein envelope (Env) trimers upon interaction with host receptors. The entry stoichiometry (T) defining the number of Env trimers required for fusion remains elusive. Stoichiometry was previously estimated using mathematical modeling of infectivity curves of pseudoviruses surface-decorated with heterotrimers containing wild-type and entry-deficient Env. Nevertheless, previous models rarely co-considered inter-protomer opening cooperativity (S, reflecting how CD4-induced conformational changes in one protomer affect the opening of adjacent protomers) and virion trimer number distributions, while experiments were limited to pseudoviruses. Here, we factored these two parameters into our models and included replication-competent virions. We provided simultaneous estimates of T and S under varying trimer number distributions and offered 2D stoichiometry maps for different Env strains. Our results depicted the interplay between viral infectivity and stoichiometry tuned by the number of trimers per virion. The estimates for all tested Env strains were prevalently higher (T ≥ 7 for BG505 or JR-FL, T ≥ 13 for NL4-3) than reported. A high degree of inter-protomer opening cooperativity was observed for the neutralization-sensitive NL4-3, while neutralization-resistant BG505 and JR-FL showed a low to intermediate degree. Entry stoichiometry and opening cooperativity were strikingly positive-correlated, implying tied inter-protomer and inter-Env cooperative interactions. Our findings provided an in-depth view of Env cooperativities during HIV-1 entry.IMPORTANCEThe sparsely distributed envelope (Env) trimers on the surface of HIV-1 work collaboratively to mediate viral entry into the host, the early step of infection. The number of interacting trimers with host receptors required for entry awaits elucidation. Here, we explored the cooperative interplay among and within Env trimers, shedding light on a previously overlooked dimension of HIV-1 entry. For the first time, we presented distributions of estimated parameters depicting the number of Env trimers and degrees of inter-protomer opening cooperativities using biologically relevant mathematic models combined with virion infectivity measurements. Our results demonstrated that the quantity of required functional trimers positively correlates with inter-protomer opening cooperativity, a feature conserved across various strains. Our findings underscore cooperative behavior as an inherent characteristic of Env dynamics during HIV-1 entry. These insights enhance our understanding of HIV-1 infection mechanisms and could inform strategies for developing effective inhibitors or neutralizing agents.